Estimate Different Bioagent as A Biofertilizer with Two Level From Chemical Fertilizer on Wheat Crop Improvement - Esmael Majed, Rafal; Ali Hadwan, Hamid; Adel Abed, Harb; Mansor Hamza, Montaser; Faris Hasen, Omer; Hmood Ali, Ehab (Iraqi Journal of Science, 2021)
Different formula of bioagents (Rhizobium cicceri cp-93, Azospirillum sp.,Pseudomonas fluorescence, Trichoderma harzianum ) used in this study as abiofertilizer on wheat crop with two level of chemical fertilizer (0 and 12.5kg/donm Dap) compared to 50kg/donm Dap (standard amount).the study carried outin Iraq/Diyala –Alkhales during November 2014,results showed significant increasein no. of spikes, no. of spikelet’s, length of spike ,Weight of 1000 seed and yield ofone m2 when adding (Rhizobium cicceri cp-93,Azospirillumsp+ Trichodermaharzianum +12.5 kg/donm Dap) in comparison with the 50kg/donm Dap. Otherformulas recorded same results with the treatment 50kg/Donm Dap with notsignificant differences except Wight of 1000 seed which recorded significantincreased in all formula, while (Rhizobium ciccericp-93,Azospirillumsp+ zeroDap)treatment recorded significant decrease from 50 kg Dap in the most parametersin study.